2013
DOI: 10.4085/1062-6050-47.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Skills and Abilities Required by Athletic Trainers in Hospital and Clinical Management Positions: A Delphi Study

Abstract: Context: Athletic training has expanded from traditional sportteam settings to varied settings involving active populations. Athletic trainers also use their education and abilities in administration to take on roles of management in hospitals and health care clinics.Objective: To begin to explore the knowledge, skills, and abilities needed in the emerging practice setting of health care management.Design: Delphi study. Setting: Directed surveys.Patients or Other Participants: Eight athletic trainers working a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 8 publications
0
35
0
Order By: Relevance
“…Professional and scholarly literature from several professional domains describe the importance of contextual intelligence in the workplace. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The purpose of this investigation was to explore how frequently contextual intelligence behaviors are practiced by female healthcare managers. Our findings indicate that 75%, (N=9) of the CI behaviors were practiced with very high or high frequency, with Multicultural leadership, Constructive use of influence, and Diagnoses context being the most frequently practiced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional and scholarly literature from several professional domains describe the importance of contextual intelligence in the workplace. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] The purpose of this investigation was to explore how frequently contextual intelligence behaviors are practiced by female healthcare managers. Our findings indicate that 75%, (N=9) of the CI behaviors were practiced with very high or high frequency, with Multicultural leadership, Constructive use of influence, and Diagnoses context being the most frequently practiced.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7] Contextual intelligence (CI) has been reported to be important and useful in a variety of industries relative to decision-making and leadership behaviors. Professionals and scholars in nursing, 8 educational research, 9 psychology, [10][11][12] counseling, 13 business, 14 politics, 15 athletic training, [16][17] medicine, 18 marketing, 19 teacher education, [20][21] global entrepreneurship, [22][23] and military strategy 24 have promoted contextual intelligence as a useful or even requisite skill. Each promotes CI for different reasons, but generally CI facilitates identifying external and internal influences that are not immediately obvious, helps in considering non-linear relationships, promotes a holistic perspective to resolve tensions among opposing ideas, and generates innovative outcomes.…”
mentioning
confidence: 99%
“…This implies an application of leadership that is not restricted to a specific context and requires discretion on the basis of changing situations and people. Providing this type of leadership requires contextual intelligence 13 and is described in the literature as the ability to interpret and react to changing surroundings. 14 Athletic training research has concluded that ATs need a high level of contextual intelligence, 13 which has been said to distinguish leaders from nonleaders 14 and is reported to be needed by physicians for navigating clinical complexity.…”
Section: Clarifying the Meaningful Termsmentioning
confidence: 99%
“…These settings are also highly visible, fast paced, and highrisk environments with numerous stakeholders that rely on the AT to coordinate care (Hankemeier & Manspeaker, 2018;Mazerolle & Eason, 2018). Over the past 20 years, this skillset has allowed the AT to prove their value in "emerging settings" such as hospitals and clinics; military, law enforcement, and fire departments; industrial settings and the performing arts (Games et al, 2020;Hazelbaker, 2013;Prentice, 2013;Radzak et al, 2020;Sefton & Burkhardt, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They serve a primary care coordination role in these settings often providing holistic-managed care for hundreds of athletes in their organization (Mazerolle & Eason, 2018). In both these traditional and emerging settings, such as medical practices, industrial/occupational settings, military/tactical and the performing arts, the ATs skills regarding stakeholder communication; operational efficiency; innovation with limited resources; collaboration and teamwork; work ethic and conscientiousness are highly valued (Eason, Mazerolle, Monsma et al, 2015;Eason, Mazerolle, Pitney et al, 2015;Hazelbaker, 2013;Nolton et al, 2019;Pecha, 2020;Prentice, 2013;Westerman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%